Impact of a Sleep Enhancement Protocol on Nighttime Room Entries in an Inpatient Rehabilitation Facility. Issue 4 (July 2021) - Sullan, Molly J.; Patel, Bhumi B.; Bauer, Russell M.; Jaffee, Michael S.
Abstract: Purpose: This study examined whether a sleep enhancement protocol (SEP) could reduce nighttime room entries (NREs) for patients with orthopedic injury (OI) or acquired brain injury (ABI) in an inpatient rehabilitation facility. Design: A two-wave prospective study assessing standard of care (SOC) versus SEP. Methods: Sixty-five participants completed baseline and follow-up questionnaires and wore an actigraph for approximately 7 days. In the SEP, nighttime care was "bundled." Findings: In SOC, NREs were associated with less efficient sleep and greater daytime fatigue. Nighttime room entries were approximately 50% lower in the SEP than SOC. Participants in the OI SOC had more room entries than any other group. There were no significant changes in room entries in the ABI SEP group. Conclusions: There was a relationship between NREs and sleep. The SEP was effective at reducing NREs for patients with OI, but not ABI. Clinical Relevance: Sleep enhancement protocols in inpatient rehabilitation facilities may be effective at improving sleep. Future research may focus on developing individualized protocols to improve sleep across patients with a variety of presenting diagnoses.